Pengaruh Motivasi Dan Kepuasan Kerja Penjawat Awam Di Majlis Bandaraya Alor Setar (Mbas) - Teh, Pei Shan (2018)
Human resource development is very crucial to an organization. Motivation and job satisfaction are two important aspects in the development of human resources that could influence the levels of job performance. This study examines motivation and job satisfaction among civil servants as well as their influence on job performance. The types of motivation examined by this study are public service motivation and work motivation, which also includes intrinsic and extrinsic work motivation. Meanwhile, job satisfaction evaluated by this study is influenced by intrinsic and extrinsic factors. Most studies on the performance of civil servants only focus on job motivation and job satisfaction. But this study also examines public service motivation that has been overlooked by researchers who examine the performance of civil servants. Civil servants play a crucial role in providing services to the public in order to spur national development as well as to improve the well-being of the society. Civil servants serving in the local government are the subjects of this study. The main reason underpinning this selection is that these civil servants are at the forefront in resolving daily problems faced by the people and hence their jobs are full of challenges. This study selected the Alor Setar City Council as a case study. A total of 261 civil servants were selected as respondents of a questionnaire survey. A total of 10 respondents who had answered the questionnaire and 5 directors of department or heads of division were selected for interviews.